Photocatalytic Activity of Nickel Doped CoO Nanocomposite for the Degradation of Azure A Dye - Singh, Nirmal; Kumar Rai, Avinash; Vyas, Ritu; Ameta, Rameshwar (Asian Journal of Chemistry, 2020)
Nanocrystalline cobalt(II) oxide doped with nickel was prepared using the sol-gel method and employed as a photocatalyst for azure A dye degradation under visible light. The prepared photocatalyst was analyzed using energy-dispersive X-ray (EDX) spectroscopy, field emission scanning electron microscopy (FESEM), Fourier-transform infrared (FTIR), X-ray diffraction (XRD) and high-resolution transmission electron microscopy (HRTEM). The photocatalytic activity of Ni-doped CoO under different working parameters, like concentration, pH, dosage (Ni-doped and undoped CoO), light intensity for the degradation of azure A dye was also optimzed. It was observed that the dye degradation rate improved after doping. Approximately 76% and 85% of azure A dye was degraded within 90 min through undoped and Ni-doped CoO, respectively.